Pengaruh Pelapisan Emulsi Minyak Wijen dan Minyak Sereh Terhadap Mutu dan Masa Simpan Buah Tomat (Lycopersicon esculentum Mill) - Prastya, Oki Adhi; Utama, I Made Supartha; Yulianti, Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 3 No 1 (2015): Maret, 2015)
The purpose of this study was to determine the effect of different concentrations of sesame and lemongrass oils emulsion in water as coating materials on quality of tomato fruits during storage at room temperature. The concentration of sesame oil emulsionwas varied 0%, 0.5%, and 1% in combination of lemon grass oil of 0%, 0.5%, 1%, and 1.5%. Additional materials used to make the emulsion were 1% of polysorbate 80, 0.5% oleic acid, and ethanol3%. Control fruits without treatments were also prepared for comparison. The experiment was performed using a Completely Randomized Design (CRD) with three replications. The results showed that treatment of a mixture of sesame oil and lemongrass oil significantly affected the quality and storagelife of the tomato fruits. The combined concentration of 0.5% sesame oil and 0.5% of lemongrass oil gave the best result which was able to reduce the weight loss, spoilage damages, change of pH and total soluble solidof the fruit juice, and texture (hardness)
Keywords: tomato, sesame oil, lomongrass oil, quality, save time, concentration